Mesoporous silica nanoparticles for stimuli-responsive controlled drug delivery: advances, challenges, and outlook - Song Y (Dove Medical Press, 2016)
Yuanhui Song, Yihong Li, Qien Xu, Zhe Liu Wenzhou Institute of Biomaterials and Engineering (WIBE), Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China Abstract: With the development of nanotechnology, the application of nanomaterials in the field of drug delivery has attracted much attention in the past decades. Mesoporous silica nanoparticles as promising drug nanocarriers have become a new area of interest in recent years due to their unique properties and capabilities to efficiently entrap cargo molecules. This review describes the latest advances on the application of mesoporous silica nanoparticles in drug delivery. In particular, we focus on the stimuli-responsive controlled release systems that are able to respond to intracellular environmental changes, such as pH, ATP, GSH, enzyme, glucose, and H2O2. Moreover, drug delivery induced by exogenous stimuli including temperature, light, magnetic field, ultrasound, and electricity is also summarized. These advanced technologies demonstrate current challenges, and provide a bright future for precision diagnosis and treatment. Keywords: mesoporous silica nanoparticle, drug delivery system, controlled release, stimuli-responsive, chemotherapy